THE MAIN OBJECTIVE IN ENERGY SUPPLY IS TO ENSURE UNINTERRUPTED AND LONG-TERM OPERATION OF TRANSFORMERS - Aripov Nuritdin Yusupovich (International Journal of Innovations in Engineering Research and Technology, 2022)
This article discusses the importance of transformers in the power supply, as well as the issues of timely maintenance of transformers, which can be achieved using special equipment.